Stabilization of water-in-water emulsion upon solvent shifting - Céré, Claire; Béven, Laure; Douliez, Jean-Paul (Frontiers in Soft Matter, 2023)
We report the stabilization of all-aqueous droplets upon addition of ethanol, which were further transformed into robust capsules. An all-aqueous emulsion consisting of Dextran (Dex)-rich droplets in a polyethylene glycol (PEG)-rich continuous phase was used as templates. Addition of ethanol induced gelation of dextran, forming aggregated pellets of poor interest. However, this feature was prevented by initially adding bovine serum albumin (BSA) or positively charged silica particles so that in this case, stable droplets formed upon solvent addition, which no longer coalesced with time. An alternative method consisting of pouring concentrated Dex solution in a mixture of PEG, ethanol and BSA or particles, also afforded stable droplets. These stable droplets were further converted into robust capsules, using carbodiimide chemistry or sililation. We expect this method for preparing capsules to be of interest for various applications in the field of microencapsulation.